Substrate stiffness and pressure alter retinal Müller glia response and extracellular matrix production - Laura Prieto-López; Xandra Pereiro; Emilio J. González Ramírez; Noelia Ruzafa; Alicia Alonso; Kristian Franze; Elena Vecino (Biomaterials and Biosystems, 2025)
Background: The retina is highly influenced by its mechanical environment, with Müller glia (MG) acting as key mechanosensors and extracellular matrix (ECM) producers. This study examined MG responses to substrate stiffness and high pressure (HP), and whether TGF-β1 modulation could mitigate these effects. Methods: Primary MG from adult rat retinas were cultured on glass (Young’s modulus E’=∼1 gigapascal (GPa)) and polyacrylamide gels (10 kPa and 100 kPa). MG were exposed to atmospheric and 70 mmHg (HP) conditions, with TGF-β1 pharmacologically blocked. Results: On glass and 100 kPa gels, MG survival, cell area, and ECM deposition (collagen I, IV, and fibronectin) increased, with cells adopting a fusiform shape and more dedifferentiated state. Under HP, survival decreased on stiffer substrates, though cell area and morphology remained unchanged. HP increased ECM deposition, which was reduced by TGF-β1 inhibition. Conclusions: Our findings suggest that MG response to mechanical stress alter their survival and cell area, and increases ECM secretion, highlighting TGF-β1 as a potential therapeutic target.